Options to Revise Reporting Guidelines for Annex I and non-Annex I National Communications - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2010)
This paper outlines options for new reporting guidelines for national communications from Annex I and non-Annex I countries, both for "full" national communications and biennial "updates". These reports can facilitate the sharing of information between Parties and may be used to assess the implementation of actions and progress towards the Convention's objectives. There are significant gaps in the current climate reporting framework. These gaps are particularly marked for non-Annex I countries in terms of GHG emissions and trends, mitigation and adaptation actions. There are also gaps in terms of the effect of mitigation actions and support provided and received for climate-related activities, including for technology transfer and capacity building. This paper suggests that: (i) national communications be produced more frequently while their focus is streamlined; (ii) reporting guidelines be revised to improve transparency about mitigation commitments/actions/targets that countries have indicated to the international community as well as other obligations taken under the UNFCCC and subsequently; (iii) standard reporting formats be used for more of the information in national communications; (iv) a flexible reporting framework be established for non-Annex I countries, where the information in (and possibly timing of) national reports is "tiered" according to national circumstances; (v) an increased emphasis be placed on reporting of "key" issues; (vi) information routinely provided on adaptation measures and policies be formalised; (vii) reporting on "support" be increased and its structure improved; and (viii) in reports from non-Annex I countries, the provision of information that is already routinely provided be formalised